The Influence of Community Empowerment In The Development of Andaliman Agro-tourism In Taman Eden 100 - Donny Ivan Samuel Simatupang; Helena Tatcher Pakpahan; Old Fandri (International Journal of Educational Research & Social Sciences, 2021)
This study aims to describe the influence of community empowerment in the development of andaliman agro-tourism in Taman Eden, Tobasa Regency. The empowerment in question is in the form of a concept to give greater responsibility to people about how to do work using andaliman plants as added value for the community. Empowerment will be successful if it is carried out in a structured manner by building a good work culture. The concept of empowerment is related to the notion of community development and community-based development. The method used in this research is the interview method to find out the benefits of empowerment carried out for the community.